2013
DOI: 10.1002/cbdv.201200222
|View full text |Cite
|
Sign up to set email alerts
|

Essential‐Oil Composition of Helichrysum italicum (Roth) G.Don ssp. italicum from Elba Island (Tuscany, Italy)

Abstract: The composition of 21 essential-oil samples isolated from Helichrysum italicum collected in seven locations of Elba Island (Tuscany, Italy), characterized by different soil types, during three different periods (January, May, and October 2010) was determined by GC-FID and GC/EI-MS analyses. In total, 115 components were identified, representing 96.8-99.8% of the oil composition. The oils were characterized by a high content of oxygenated monoterpenes (38.6-62.7%), while monoterpene and sesquiterpene hydrocarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 18 publications
4
28
0
2
Order By: Relevance
“…Curcumene isomers were found in a high concentration if plant was collected in winter period. These results are similar with those published by Paolini et al (2006) and Leonardi et al (2013) for plant material collected in Tuscany, as well as in Sardinia (Bianchini et al 2003).…”
Section: Resultssupporting
confidence: 94%
“…Curcumene isomers were found in a high concentration if plant was collected in winter period. These results are similar with those published by Paolini et al (2006) and Leonardi et al (2013) for plant material collected in Tuscany, as well as in Sardinia (Bianchini et al 2003).…”
Section: Resultssupporting
confidence: 94%
“…Consequently, studies reporting its composition are numerous (Angioni et al, 2003;Bertoli et al, 2012;Bianchini et al, 2009;Bianchini et al, 2004;Bianchini et al, 2003;Bianchini et al, 2001;Conti et al, 2010;Leonardi et al, 2013;Mancini et al, 2011;Mastelic et al, 2008;Mastelic et al, 2005;Morone-Fortunato et al, 2010;Paolini et al, 2006;Perrini et al, 2009;Roussis et al, 2000;Satta et al, 1999;Usai et al, 2010 (Bianchini et al, 2001;Paolini et al, 2006), another constituted by a high amount of geraniol and geranyl acetate (Bianchini et al, 2001;Morone-Fortunato et al, 2010), and a third one with a large proportion of sesquiterpenes (Bianchini et al, 2001;Morone-Fortunato et al, 2010). Regarding H. italicum subsp.…”
Section: Plant Extracts and Chemical Compositionmentioning
confidence: 99%
“…The major terpenes found in EOs are the monoterpenes (C 10 ), but they also contain sesquiterpenes (C 15 ) or even traces of some diterpenes (C 20 ). These compounds are common in essential oils of different plants from diverse families including Asteraceae (Leonardi et al, 2013), Lamiaceae (Herraiz-Peñalver et al, 2015), Pinaceae (Sadeghi et al, 2013), Solanaceae (Murungi et al, 2013), etc. Additionally, recent studies have suggested that the addition of micronutrients and the inoculation of aromatic plants with mycorrhiza can enhance the production of different terpenes as well as other secondary metabolites, increasing the yield of biocidal compounds from natural sources (Yadegari, 2015;Jugran et al, 2015).…”
Section: Introductionmentioning
confidence: 99%